Teaching management, spirituality, and religion: André Delbecq as a pioneer. Issue 1 (1st January 2020) - Allen, Stuart; Williams, Peter
ABSTRACT: André Delbecq is remembered as a pioneer for his groundbreaking courses on spirituality for executive leaders. He generously shared his experiences with other educators in multiple presentations and articles beginning in the late 1990s. His writings provide insight into the content of his classes and practical teaching approach in the classroom. In this article and the accompanying video, edited from an interview with André in 2015, we provide an overview of André's entry into teaching management, spirituality, and religion, and we reflect on his teaching philosophy. The video provides the reader with a glimpse of André's warmth, passion, and wisdom on this topic. His work and approach stand as a guiding light for those similarly interested in preparing leaders for the spiritual challenges of leadership roles.